Review of biochar for the management of contaminated soil: Preparation, application and prospect - Yuan, Peng; Wang, Jianqiao; Pan, Yijun; Shen, Boxiong; Wu, Chunfei (The Science of the total environment, 2019)
As a multi-beneficial amendment, biochar is reasonable and reliable to be employed as an amendment to implement soil remediation. An overview on the manufacture, applications for contaminated soil restoration and revegetation, as well as recommended aspects for future work has been accomplished. One of the objectives of this work presented herein was to determine the effect of feedstock and preparation conditions such as pyrolysis temperature, retention time, gas flow rate, additives on the biochar characteristics and application potentials. Besides, relevant modification or activation technologies have been discussed for the improvement of the biochar functions. The application of biochar could adjust the soil structure (surface area, pore size and distribution etc.), improve the soil physicochemical properties (pH, cation exchange capacity, water retention capacity etc.) and enhance the uptake of soil nutrients for plant growth; In addition, it also can be used to adsorb various contaminants (heavy metals, organic matters), modify the habit and function of microorganism and mitigate climate problem by changing the bioavailability of elements (C, N, K etc.) in soil. These results also provided the possibility to expend the application of biochar to modify the degraded soils in the saline-alkali soil and industrial regions, further increase the usable area of cultivated land. The future research directions could be suggested as long-term field trials, the evaluation of environmental risk and the optimization of biochar production. Moreover, the relevant mechanisms should be adequately considered for maximizing the all-around efficiency of biochar amendments. [Display omitted] •An overview on the soil remediation by biochar has been accomplished.•Feedstock and production conditions affected the properties and functions of biochar.•Biochar modifiers had multiple benefits for the diverse soil management purposes.•Challenges and prospects of restoring degraded soil by biochar have been illustrated.•Optimization of the soil remediation based on biochar should be considered further.